2017
DOI: 10.1111/sms.12876
|View full text |Cite
|
Sign up to set email alerts
|

Secular and longitudinal physical activity changes in population‐based samples of children and adolescents

Abstract: The aims of this study were to investigate whether physical activity (PA) and sedentary time (ST) in 9-and 15-year-olds differed between 2005-2006 and 2011-2012 (secular change), and to investigate changes in PA and ST from age 9 to 15 (longitu- decline in PA in the participants followed longitudinally from age 9 to 15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
82
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 33 publications
13
82
2
3
Order By: Relevance
“…Dalene et al. produced similar results to us, reporting negative temporal trends in physical activity, which they attributed to less active transportation to and from school, increased screen‐based sedentary behaviour and decreased leisure activities and organised sports.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Dalene et al. produced similar results to us, reporting negative temporal trends in physical activity, which they attributed to less active transportation to and from school, increased screen‐based sedentary behaviour and decreased leisure activities and organised sports.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, a study by Dalene et al. showed that sedentary time among 9‐ and 15‐year‐olds increased from 2005–2006 to 2011–2012. At the same time, their levels of light physical activity, which is the level below moderate‐to‐vigorous physical activity, had decreased by approximately 30 minutes per day.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes and its treatment therefore appear to promote excess weight gain. Several factors, which are common in adolescents with or without T1D, such as sedentary behavior, reduced exercise (especially in females), and unhealthy eating habits, may contribute to favor a positive energy balance . Other factors favoring body fat accumulation are specific to diabetes, including extra calorie intake to prevent or correct hypoglycemia, the consumption of low carbohydrate high fat foods, to reduce postprandial glucose increase, and the chronic exposure of the peripheral tissues to non‐physiologic hyperinsulinemia due to the subcutaneous insulin injections or infusion via insulin pump .…”
Section: Discussionmentioning
confidence: 99%
“…National and international guidelines recommend that children and adolescents engage in regular physical activity, of moderate‐to‐vigorous intensity, for at least 60 minutes per day; however, many adolescents do not meet this quantity or quality . OSP has the potential to help adolescents establish lifelong, healthy physical activity patterns .…”
Section: Discussionmentioning
confidence: 99%